Maximizing Employee Performance through Rewards, Culture, and Training: Memaksimalkan Kinerja Karyawan melalui Penghargaan, Budaya, dan Pelatihan - Ridwan Purnomo; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of rewards, organizational culture, and training on employee performance at PT Harapan Sejaterah Karya Utama. Through quantitative analysis, utilizing primary data from distributed questionnaires and secondary data from relevant sources, the research reveals that rewards, organizational culture, and training individually and collectively positively influence employee performance. The findings underscore the importance of providing rewards such as additional salary and bonuses for achieving targets, enhancing organizational culture to foster a conducive work environment, and promoting open communication between employees and management. These implications offer actionable insights for organizations, facilitating the optimization of employee performance and overall organizational success. Highlight: Rewards, culture, and training enhance employee performance significantly. Open communication fosters synergy between employees and management. Optimization leads to improved organizational success. Keyword: Rewards, Organizational Culture, Training, Employee Performance, PT Harapan Sejaterah Karya Utama